ANALISIS SEMIOTIKA PADA ILUSTRASI SAMPUL MAJALAH TEMPO BERTEMA TERORISME EDISI 13 – 27 MEI 2018 - Wahyudi, Luqman; Purnomo, Aji Susanto Anom (Jurnal Bahasa Rupa, 2022)
The cover of Tempo weekly magazine is known to be bold, critical, and sometimes controversial with its hidden meanings that are intentionally inserted (subliminal messages) in all fields (social, political, economic). This study was conducted to analyze the meanings and messages contained in a sample of three covers of Tempo magazine editions of 13, 20 and 27 May 2018 which featured terrorism cases, through three elements of Charles Sanders Peirce's semiotics, namely ground, object, and interpretant. The methodology used in this research is qualitative interpretative using semiotic analysis method. The results of this study are that the meaning of the sign that appear on the cover are closely related to acts of terrorism, prisoners who take hostage at the Brimob Mako detention house, a small child who is a suspect in a suicide bombing with his family, and students who stabbed Brimob intelligence officers in Kelapa Dua.The conclusion of researcher's interpretation when looking at the cover illustration is to disclosure  a series of terrorist acts in the May 2018.